Enhancing student participation in "group discussions" within English lessons in a Chinese institution of higher education - Liu, Ying (Auckland University of Technology, 2006)
The aim of this study was to investigate factors enhancing Chinese tertiary students’ active participation in English group discussion. In China, tertiary students are encouraged to read, write and listen to the English language. Despite at least eight years of learning English, most students still cannot communicate effectively in English. This phenomenon has been described in China as ‘Dumb English’. The Government and tertiary educators recognised the problem reforming the curriculum and related educational policy. One of the main reforms has been the inclusion of ‘group discussion’ into the learning of English. However, despite this initiative to date many students have remained passively silent in these discussions, thus decreasing the discussion’s effectiveness in promoting spoken English fluency. This qualitative and interpretive research utilised the appreciative inquiry (AI) research approach in designing the research process. Data from the interviews of eighteen tertiary students was summarised into provocative propositions and developed from there into an action plan for use in the English education in China. The findings of this study included the discussion topic, the characteristics of the group members, and teacher’s roles were the three most important factors enhancing active participation in the ‘group discussion’. Provocative propositions, summarising the common themes emerging in the findings, were constructed. For example, most students were interested in simple, practical and familiar discussion topics. Based on the propositions, I explored an action plan outlining suggestions for English teachers in Chinese higher institutions to enhance their student’s active participation in group discussion. I have surmised that student’s active participation in English group discussions can be effectively increased by attending to discussion topics, student group characteristics and the teacher’s roles. Simple and practical discussion topics, familiar and interactive group members and a teacher who often encourages students, knowing how to assist the learners effectively are all important factors that enhance student’s participation in group discussions. Increased participation is likely to result in improved English fluency amongst Chinese students. I outlined some of the highlights and benefits of the study such as the importance of the discussion topic for second language learners, the characteristics of more successful student groups, and the importance of the teacher’s role in facilitating group discussions. By contrast some limitations of this research included the similarity of the student’s responses as this might suggest a limited range of students, as well as having all the participants from one institution. Finally, I made some recommendations for improvement in practice.
Keywords: Discussion; English language -- Spoken English -- Study and teaching -- China